Extended conjugated microporous polymers for photocatalytic hydrogen evolution from water - Sprick, Reiner Sebastian; Bonillo, Baltasar; Sachs, Michael; Clowes, Rob; Durrant, James R; Adams, Dave J; Cooper, Andrew I (Chemical communications (Cambridge, England), 2016)
Conjugated microporous polymers (CMPs) have been used as photocatalysts for hydrogen production from water in the presence of a sacrificial electron donor. The relative importance of the linker geometry, the co-monomer linker length, and the degree of planarisation were studied with respect to the photocatalytic hydrogen evolution rate. Conjugated microporous polymers (CMPs) have been used as photocatalysts for hydrogen production from water in the presence of a sacrificial electron donor.